Method for efficiently recycling waste plastics

By using specific organic compound modifiers and additives in the recycling of waste plastics, combined with advanced processing technology, the problems of limited performance improvement, high energy consumption, high cost and possible introduction of new pollutants in the existing technology are solved, and high performance, low cost and environmentally friendly recycled plastic products are achieved.

CN119823439APending Publication Date: 2025-04-15DONGGUAN ZHONGYI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510104626.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing technology has problems such as limited performance improvement, high energy consumption, high cost and possible introduction of new pollutants in the recycling of waste plastics. It is urgent to develop innovative, efficient and environmentally friendly recycling technologies.

Method used

Specific organic compound modifiers and additives are used, combined with ultrasonic, microwave, high-voltage pulsed electric field and other technical means, and high-speed premix and melt blending are carried out, and high-performance recycled plastic products are made through multi-scale fiber reinforcement and enzyme catalytic degradation and repolymerization processes.

Benefits of technology

It significantly improves the mechanical, electrical, barrier properties of recycled plastics, reduces energy consumption and production costs, and improves the environmental protection performance and economic benefits of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255092690000261
    Figure BDA0005255092690000261
  • Figure BDA0005255092690000271
    Figure BDA0005255092690000271
  • Figure BDA0005255092690000281
    Figure BDA0005255092690000281
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly materials, and particularly discloses a waste plastic recycling method which comprises the following steps: selecting one or a mixture of more of waste PET (Polyethylene Terephthalate), PP (Polypropylene), PVC (Polyvinyl Chloride), PS (Polystyrene) and PC (Polycarbonate) as a base material; adding organic silicon-graphene, a bio-based polyester-carbon nanotube composite modifier and a reinforcing agent, wherein the addition amount is 3-8% of the weight of the base material; flame-retardant and antioxidant auxiliaries are matched; the method comprises the following steps: carrying out plasma and enzyme catalysis pretreatment on waste plastic, premixing with other components by a high-speed mixer, carrying out melt blending in a double-screw extruder under the assistance of supercritical fluid, promoting dispersion by ultrasonic and microwave during the period, and simultaneously carrying out photo-initiation in-situ polymerization; finally, a product is prepared through injection molding, extrusion and other molding processes. The performance of the waste plastic recycled material is greatly improved, the mechanical performance, the electrical performance, the barrier performance and the like of the recycled material are remarkably improved, and the waste plastic recycled material can be widely applied to more fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmentally friendly materials, and in particular to a method for efficiently recycling waste plastics. Background Art

[0002] With the widespread use of plastic products, the large amount of waste plastics has posed a serious threat to the environment. Traditional methods of dealing with waste plastics, such as landfill, occupy a large amount of land resources, and plastics are difficult to degrade in the long term, polluting the soil and groundwater; incineration releases harmful gases and pollutes the atmospheric environment. Although existing recycling technologies can alleviate these problems to a certain extent, there are still problems such as limited improvement in the performance of recycled plastics, high energy consumption and cost in the recycling process, and the possible introduction of new pollutants. Therefore, there is an urgent need to develop an innovative, efficient, and environmentally friendly technology for recycling waste plastics. Summary of the invention

[0003] The present invention provides a method for recycling waste plastics, comprising:

[0004] One or more of discarded polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), polyvinyl chloride (PVC), polystyrene (PS), and polybutylene terephthalate (PBT) are selected as the base material;

[0005] A specific organic compound modifier is added to the base material, wherein the modifier is 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid (MAPBA), 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid (BMOPA), 3-(2-vinyl-3-acryloyloxy)methyl benzoate (VAPMB), 4-(3-methyl-2-butenoyloxy-2-ethoxy)phenylpropionic acid ethyl ester (MBEPP), 3-(4-vinyl-3-acryloyloxy)butyl benzoate (VAPBB), 4-(3-acryloyloxy- One or more of propyl 2-propoxy)phenylacetate (APPPA), propyl 3-(2-methyl-3-butenoyloxy)benzoate (MBPBA), butyl 4-(3-vinyl-2-acryloyloxy)phenylpropionate (VABPB), ethyl 3-(4-methyl-3-butenoyloxy)benzoate (MBEBA), methyl 4-(3-acryloyloxy-2-ethoxy)phenylacetate (AEPPM), and isopropyl 3-(2-acryloyloxy-3-methoxy)benzoate (APMIB), the addition amount is 4-10% by weight of the base material;

[0006] Mixed with specific additives, the additives include magnesium hydroxide-aluminum hydroxide-phosphate melamine salt compound flame retardant or magnesium hydroxide-aluminum hydroxide compound flame retardant (added amount is 8-12% of the weight of the base material), one or more reinforcing agents of glass fiber, carbon fiber, aramid fiber (added amount is 4-8% of the weight of the base material), ultraviolet absorber (added amount is 2-4% of the weight of the base material), antioxidant (added amount is 1-3% of the weight of the base material), light stabilizer (added amount is 2-4% of the weight of the base material);

[0007] After the waste plastic is crushed into a particle size of 1-6 mm, it is premixed with other components at a high speed of 1000-1500 rpm for 30-40 minutes, and then melt-blended in a twin-screw extruder at 160-260° C. at a screw speed of 150-180 rpm. During the blending process, ultrasonic waves (power 200-250 W, processing time 15-25 minutes), microwave radiation (power 500-700 W, processing time 15-20 minutes), high-voltage pulse electric field (electric field strength 2.5-3.5 kV / cm, pulse frequency 18-22 Hz, processing time 18-22 minutes), ultrasonic and microwave alternating treatment (ultrasonic wave power 200-250 W, microwave power 500-700 W, each processing time 5-8 minutes, alternating 3-4 times) and the like are used to promote dispersion and reaction, and finally the recycled plastic products are made through injection molding, extrusion molding, extrusion blow molding, compression molding and other processes.

[0008] Furthermore, the organic compound modifier 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid (MAPBA) is synthesized by using 3-hydroxybenzoic acid and 2-methyl-3-chloropropene as raw materials, heating and refluxing for 4-6 hours under alkaline conditions to generate 3-(2-methyl-3-hydroxypropoxy)benzoic acid, and then reacting with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain the obtained product.

[0009] Furthermore, the synthesis method of the organic compound modifier 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid (BMOPA) is as follows: 4-hydroxyphenylacetic acid and 3-butenoyl chloride are used as raw materials, reacted at 0-10° C. for 2-3 hours in the presence of triethylamine to generate 4-(3-butenoyloxy)phenylacetic acid, and then heated and refluxed with 2-methoxy-3-chloropropane under alkaline conditions for 3-5 hours to obtain the obtained product.

[0010] Furthermore, the synthesis method of the organic compound modifier 3-(2-vinyl-3-acryloyloxy) methyl benzoate (VAPMB) is as follows: using 3-hydroxybenzoic acid methyl ester and 2-vinyl-3-chloropropylene as raw materials, heating and refluxing for 5-7 hours under alkaline conditions to generate 3-(2-vinyl-3-hydroxy) methyl benzoate, and then reacting with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain the obtained product.

[0011] Furthermore, the synthesis method of the organic compound modifier 4-(3-methyl-2-butenoyloxy-2-ethoxy)benzenepropionic acid ethyl ester (MBEPP) is as follows: 4-hydroxybenzenepropionic acid ethyl ester and methyl-2-butenoyl chloride are used as raw materials, reacted at 0-10°C for 2-3 hours in the presence of triethylamine to generate 4-(3-methyl-2-butenoyloxy)benzenepropionic acid ethyl ester, and then heated and refluxed with 2-ethoxy-3-chloropropane under alkaline conditions for 4-6 hours to obtain the obtained product.

[0012] Furthermore, the synthesis method of the organic compound modifier 3-(4-vinyl-3-acryloyloxy) butyl benzoate (VAPBB) is as follows: 3-hydroxybutyl benzoate and 4-vinyl-3-chloropropylene are used as raw materials, heated under alkaline conditions for reflux reaction for 6-8 hours to generate 3-(4-vinyl-3-hydroxy) butyl benzoate, and then reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain the obtained product.

[0013] Furthermore, the synthesis method of the organic compound modifier 4-(3-acryloyloxy-2-propoxy)phenylacetic acid propyl ester (APPPA) is as follows: 4-hydroxyphenylacetic acid propyl ester and acryloyl chloride are used as raw materials, reacted at 0-10° C. for 2-3 hours in the presence of triethylamine to generate 4-(3-acryloyloxy)phenylacetic acid propyl ester, and then heated and refluxed with 2-propoxy-3-chloropropane under alkaline conditions for 4-6 hours to obtain the product.

[0014] Furthermore, the synthesis method of the organic compound modifier 3-(2-methyl-3-butenoyloxy)propyl benzoate (MBPBA) is as follows: 3-hydroxypropyl benzoate and 2-methyl-3-butenoyl chloride are used as raw materials, and reacted at 0-10° C. for 2-3 hours in the presence of triethylamine to obtain the obtained product.

[0015] Furthermore, the synthesis method of the organic compound modifier 4-(3-vinyl-2-acryloyloxy)benzenepropionic acid butyl ester (VABPB) is as follows: 4-hydroxybenzenepropionic acid butyl ester and 3-vinyl-2-chloropropylene are used as raw materials, and refluxed under alkaline conditions for 5-7 hours to generate 4-(3-vinyl-2-hydroxy)benzenepropionic acid butyl ester, and then reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain the obtained product.

[0016] Furthermore, the synthesis method of the organic compound modifier 3-(4-methyl-3-butenoyloxy)ethyl benzoate (MBEBA) is as follows: 3-hydroxyethyl benzoate and 4-methyl-3-butenoyl chloride are used as raw materials, and reacted at 0-10° C. for 2-3 hours in the presence of triethylamine to obtain the obtained product.

[0017] Beneficial effects:

[0018] The present invention greatly improves the performance of waste plastic recycled materials through a variety of innovative means. The recycled materials have significantly improved mechanical, electrical, barrier and other properties, and can be widely used in more fields. The use of environmentally friendly materials such as bio-based polyester-carbon nanotube composite reinforcing agents improves the environmental performance of the materials and reduces potential harm to the environment. At the same time, the supercritical carbon dioxide-assisted reaction extrusion process reduces the processing temperature and pressure and reduces energy consumption. The enzyme-catalyzed degradation and repolymerization regulation process realizes the controllable regeneration of waste plastics and reduces the discharge of waste. By optimizing the process and using low-cost raw materials, the cost of recycling waste plastics is reduced. Using common waste plastics as the base material and combining the modifier synthesized from simple compound raw materials, the performance of the recycled materials is significantly improved without increasing too much cost, and the economic benefits are improved. The microencapsulated phase change material toughening and temperature adjustment technology enables the recycled materials to adjust their own temperature when the temperature changes, broadening its application range. The magnetic nanoparticle-polyaniline composite conductive agent gives the material conductive properties and can be used in the fields of electronics and electrical appliances.

[0019] Example 1

[0020] Recipe Implementation:

[0021] The base material is 70 parts by weight of waste polyethylene terephthalate (PET).

[0022] 5 parts by weight of an organosilicon-graphene composite modifier was added.

[0023] 6 parts by weight of a bio-based polyester-carbon nanotube composite reinforcing agent was mixed in.

[0024] 4 parts by weight of nanocellulose-montmorillonite composite filler was added.

[0025] 3 parts by weight of a magnetic nanoparticle-polyaniline composite conductive agent was added.

[0026] 2 parts by weight of microencapsulated phase change material were added.

[0027] 8 parts by weight of glass fibers (macrofibers), 3 parts by weight of carbon fibers (microfibers), and 2 parts by weight of nanocellulose fibers (nanofibers) were added for multi-scale fiber reinforcement.

[0028] Introduce an appropriate amount of interfacial compatibilizer to improve the interfacial compatibility between the fiber and the waste plastic.

[0029] Process implementation:

[0030] Waste PET is modified synergistically by plasma treatment and chemical grafting.

[0031] The modified waste PET was premixed with other components in a high-speed mixer for 30 minutes.

[0032] The supercritical carbon dioxide-assisted reactive extrusion process was used to carry out melt blending in a twin-screw extruder.

[0033] During the extrusion process, light-induced in-situ polymerization modification is carried out to make the monomers polymerize in-situ on the surface and inside of the waste plastic. The injection molding process is used to make recycled plastic products.

[0034] Performance Testing:

[0035] The tensile strength reaches 85MPa, which is 40% higher than that of PET recycled materials without the technology of the present invention. The synergistic effect of the organic silicon-graphene composite modifier, the bio-based polyester-carbon nanotube composite reinforcing agent and the multi-scale fiber reinforcement significantly enhances the mechanical properties of the material.

[0036] The conductivity increased by 3 orders of magnitude to 10 -3 S / cm. The magnetic nanoparticle-polyaniline composite conductive agent gives the material good conductive properties.

[0037] In an environment with a temperature range of 10-40°C, the temperature fluctuation range of the material is controlled within 5°C. Microencapsulated phase change materials effectively achieve the regulation of material temperature.

[0038] The oxygen permeability is reduced by 50%, which improves the barrier properties of the material.

[0039] Example 2

[0040] Recipe Implementation:

[0041] The base material is waste polypropylene (PP), 75 parts by weight. Polypropylene has a wide range of sources and a large recycling volume, but its mechanical properties and functionality have certain limitations, and performance is optimized through subsequent addition of modifiers and additives.

[0042] Add 4 parts by weight of organosilicon-graphene composite modifier. Organosilicon-graphene composite modifier can utilize the low surface energy, flexibility and weather resistance of organosilicon and the excellent mechanical, electrical and thermal properties of graphene to achieve multifunctional modification of waste PP. Organosilicon improves the surface properties and flexibility of PP, while graphene enhances its mechanical, electrical and thermal properties.

[0043] 5 parts by weight of bio-based polyester-carbon nanotube composite reinforcing agent is mixed in. Bio-based polyester is renewable and degradable, and carbon nanotubes have extremely high strength and modulus. The two are combined to utilize the environmental protection characteristics of bio-based polyester and the high strength of carbon nanotubes to enhance the mechanical properties of waste PP and improve the environmental performance of the material.

[0044] 3 parts by weight of nanocellulose-montmorillonite composite filler was added. The high strength, high modulus, high specific surface area of ​​nanocellulose combined with the unique layered structure and ion exchange properties of montmorillonite can improve the mechanical properties, barrier properties and thermal stability of waste PP.

[0045] 2 parts by weight of magnetic nanoparticle-polyaniline composite conductive agent is added to achieve magnetic manipulation of the material using the magnetism of the magnetic nanoparticles, and the conductivity of polyaniline gives the waste PP conductive properties while improving the stability of the material.

[0046] Add 2 parts by weight of microencapsulated phase change material. Microencapsulated phase change material absorbs or releases heat when the temperature changes, so as to adjust the temperature of the material, improve the toughness of the material, and adjust the temperature of the material environment, thus broadening the application range of the material.

[0047] 7 parts by weight of glass fiber (macro fiber), 3 parts by weight of basalt fiber (micro fiber) and 2 parts by weight of nano silica fiber (nanofiber) were added for multi-scale fiber reinforcement. Fibers of different scales form different levels of reinforcement structures in waste PP. Nanofibers form a nano-scale reinforcement network, hindering the movement of molecular chains and improving strength and modulus; microfibers and macrofibers enhance mechanical properties on a larger scale.

[0048] Introduce an appropriate amount of interfacial compatibilizer to improve the interfacial compatibility between the fiber and the waste plastic. The interfacial compatibilizer can promote a better combination of the fiber and the waste PP, so that the fiber can more effectively transfer stress when subjected to force and give full play to the reinforcing effect.

[0049] Process implementation:

[0050] Enzyme catalytic degradation and repolymerization regulation process of waste PP. Use specific enzymes to selectively degrade waste PP, targeting polyethylene terephthalate (PET):

[0051] Enzyme used: PET hydrolase. It is an enzyme specific to PET that can efficiently recognize and cut the ester bonds in PET molecules. Its main component is protein, which is composed of a specific amino acid sequence. These amino acids are connected by peptide bonds to form protein molecules with a specific three-dimensional structure. This three-dimensional structure gives PET hydrolase a unique active site, enabling it to specifically bind to PET molecules and catalyze the hydrolysis of ester bonds.

[0052] For polypropylene (PP):

[0053] Enzymes used: Some lipases from microbial sources can degrade PP to a certain extent. These lipases are also proteins, and their amino acid composition and arrangement determine their degradation activity on PP. The active center of lipases usually contains amino acid residues such as serine, histidine and aspartic acid, which work synergistically in the catalytic process, allowing the lipase to interact with the PP molecule and achieve degradation.

[0054] For polycarbonate (PC):

[0055] Enzyme used: Carbonate esterase. This type of enzyme can catalyze the hydrolysis of carbonate bonds in PC. Its molecular structure contains some metal ions, such as zinc ions, which play a key role in the catalytic activity of the enzyme. Carbonate esterase achieves efficient degradation of PC through the synergistic effect of its specific amino acid sequence and metal ions.

[0056] The degree of degradation is precisely controlled, and then through repolymerization reaction, the degradation products are repolymerized into polymers with specific structures and properties, thus achieving controllable regeneration of waste PP.

[0057] The treated waste PP was premixed with other components in a high-speed mixer for 35 minutes. The stirring action of the high-speed mixer allows the components to be initially dispersed evenly, preparing for subsequent melt blending.

[0058] The supercritical carbon dioxide-assisted reaction extrusion process is used to melt blend in a twin-screw extruder. Supercritical carbon dioxide improves the fluidity of the material, promotes the chemical reaction, improves the dispersion uniformity of each component, and reduces the processing temperature and pressure, reducing energy consumption. The temperature of each section of the extruder is set as follows: 140-160℃ in zone 1, 160-180℃ in zone 2, 180-200℃ in zone 3, 200-220℃ in zone 4, the screw speed is 150-180rpm, the injection pressure of supercritical carbon dioxide is 10-15MPa, the flow rate is 5-10L / min, and the material residence time is 3-5 minutes.

[0059] During the extrusion process, photoinitiator in-situ polymerization modification is carried out to make the monomer polymerize in-situ on the surface and inside of the waste plastic. Photoinitiator is used to generate free radicals under light, which triggers the monomer to polymerize in-situ on the surface or inside of the waste PP, forming a polymer layer tightly bonded to the waste PP, thereby improving the performance of the waste PP.

[0060] Recycled plastic products are made by extrusion molding. Through extrusion molding, the mixed and improved materials are processed into recycled plastic products with specific shapes and sizes.

[0061] Performance Testing:

[0062] The bending strength reaches 70MPa, which is 35% higher than that of PP recycled materials without the technology of the present invention. The synergistic effect of the organic silicon-graphene composite modifier, the bio-based polyester-carbon nanotube composite reinforcement and the multi-scale fiber reinforcement significantly enhances the rigidity of the material.

[0063] The conductivity increased by 2 orders of magnitude to 10 -4 S / cm. The magnetic nanoparticle-polyaniline composite conductive agent gives the material good conductive properties and expands its application field.

[0064] In an environment with a temperature range of 10-40°C, the temperature fluctuation range of the material is controlled within 6°C. Microencapsulated phase change materials effectively control the temperature of the material and improve the stability of the material.

[0065] The oxygen permeability is reduced by 40%, which improves the barrier properties of the material. The barrier effect of nanocellulose-montmorillonite composite filler is significant and can be used in packaging and other fields that require barrier properties. Specific enzymes are used to selectively degrade waste plastics, control the degree of degradation, and then through repolymerization, the degradation products are repolymerized into polymers with specific structures and properties, realizing the controllable regeneration of waste plastics.

[0066] Example 3

[0067] Recipe Implementation:

[0068] The base material is waste polyvinyl chloride (PVC), 72 parts by weight.

[0069] 6 parts by weight of an organosilicon-graphene composite modifier was added.

[0070] 4 parts by weight of a bio-based polyester-carbon nanotube composite reinforcing agent was mixed in.

[0071] 5 parts by weight of nanocellulose-montmorillonite composite filler was added.

[0072] 3 parts by weight of a magnetic nanoparticle-polyaniline composite conductive agent was added.

[0073] 3 parts by weight of microencapsulated phase change material were added.

[0074] 6 parts by weight of glass fiber (macrofiber), 4 parts by weight of aramid fiber (microfiber) and 3 parts by weight of nano alumina fiber (nanofibers) were added for multi-scale fiber reinforcement.

[0075] Introduce an appropriate amount of interfacial compatibilizer to improve the interfacial compatibility between the fiber and the waste plastic.

[0076] Process implementation:

[0077] Waste PVC is modified by plasma treatment and chemical grafting.

[0078] The modified waste PVC was premixed with other components in a high-speed mixer for 32 minutes.

[0079] The supercritical carbon dioxide-assisted reactive extrusion process was used to carry out melt blending in a twin-screw extruder.

[0080] During the extrusion process, light-induced in-situ polymerization modification is carried out to make the monomers polymerize in-situ on the surface and inside of the waste plastic. The injection molding process is used to make recycled plastic products.

[0081] Performance Testing:

[0082] The tensile strength reaches 55 MPa, which is 42% higher than that of PVC recycled materials that do not use the technology of the present invention. The multi-scale fiber reinforcement and the bio-based polyester-carbon nanotube composite reinforcement work together to greatly enhance the internal structure of the material.

[0083] Impact strength increased by 50% to 20 kJ / m 2 The microencapsulated phase change material absorbs energy through phase change when impacted, and synergistically improves the toughness of the material with the organosilicon-graphene composite modifier.

[0084] The gas barrier property of the material is greatly improved, and the water vapor transmission rate is reduced by 40%. The barrier layer of nanocellulose-montmorillonite composite filler effectively hinders the diffusion of water vapor molecules.

[0085] In the flame retardant performance test, the limiting oxygen index increased from 25% to 29%. The organosilicon-graphene composite modifier and the nanocellulose-montmorillonite composite filler formed a more stable barrier structure at high temperature, and synergistically improved the flame retardant performance with the original flame retardant system. Compared with the modification method of PVC recycled materials in the prior art, the embodiments of the present invention increased the tensile strength by 15-20MPa and the impact strength by 5-8kJ / m 2 The gas barrier properties are significantly improved, and the limiting oxygen index is increased by 2-4 percentage points.

[0086] Example 4

[0087] Recipe Implementation:

[0088] Waste polystyrene (PS) is used as the base material, 78 parts by weight.

[0089] Add 3 parts by weight of an organosilicon-graphene composite modifier to enhance the flexibility, conductivity and mechanical properties of the material.

[0090] 5 parts by weight of bio-based polyhydroxyalkanoate-carbon nanotube composite reinforcing agent was mixed in to improve the strength and environmental performance of the material. 4 parts by weight of nanocellulose-rectorite composite filler was added to improve the barrier property and thermal stability of the material.

[0091] 2 parts by weight of magnetic nanoparticle-polypyrrole composite conductive agent is added to give the material magnetic response and conductive properties.

[0092] 2 parts by weight of microencapsulated polyethylene glycol phase change material is added to achieve temperature regulation and toughening effects.

[0093] 5 parts by weight of glass fiber (macrofiber), 3 parts by weight of carbon fiber (microfiber) and 2 parts by weight of nano titanium dioxide fiber (nanofibers) were added for multi-scale fiber reinforcement.

[0094] An appropriate amount of silane coupling agent is introduced as an interface compatibilizer to improve the interface bonding between the fiber and the waste plastic.

[0095] Process implementation:

[0096] The waste PS was subjected to microwave-plasma synergistic pretreatment at a microwave power of 600 W and a plasma power of 200 W for 8 minutes to improve the surface activity of the material.

[0097] The pretreated waste PS was premixed with other components in a high-speed mixer at a rotation speed of 1200 rpm for 35 minutes.

[0098] A supercritical nitrogen-assisted reactive extrusion process was adopted. In a twin-screw extruder, the supercritical nitrogen pressure was 12 MPa, the flow rate was 8 L / min, the extruder temperature was 150-170°C in zone 1, 170-190°C in zone 2, 190-210°C in zone 3, 210-230°C in zone 4, and the screw speed was 160 rpm.

[0099] During the extrusion process, photoinitiated in-situ polymerization was performed using a wavelength of 380 nm and a light intensity of 15 mW / cm 2 The waste plastic was irradiated with ultraviolet light for 20 minutes to initiate polymerization of the monomers on the surface and inside of the waste plastic.

[0100] The recycled plastic products are made by injection molding process.

[0101] Performance Testing:

[0102] The tensile strength reaches 48MPa, which is 38% higher than that of PS recycled materials without the technology of the present invention. The multi-scale fiber reinforcement and the composite reinforcement agent work together to strengthen the internal structure of the material.

[0103] The thermal stability is significantly improved, and the temperature at which the thermal weight loss is 5% is increased by 25°C. The nanocellulose-rectorite composite filler and the organosilicon-graphene composite modifier jointly improve the thermal stability of the material.

[0104] In a simulated natural environment aging test, after 1,200 hours of light, temperature and humidity changes, the mechanical property retention rate of the material reached 78%, while that of ordinary PS recycled materials was only 55%. Microencapsulated polyethylene glycol phase change material and silicone-graphene composite modifier enhanced the material's weather resistance.

[0105] The surface resistance of the material is reduced to 10 7 Ω, with good antistatic properties. Magnetic nanoparticles-polypyrrole composite conductive agent effectively improves the electrical properties of the material.

[0106] Compared with the conventional modification method of PS recycled materials in the prior art, the embodiments of the present invention improve the tensile strength by 12-18 MPa, significantly improve the thermal stability, and increase the mechanical property retention rate after aging by 15-20%.

[0107] Example 5

[0108] Recipe Implementation:

[0109] The base material is 75 parts by weight of waste polycarbonate (PC) and polyethylene terephthalate (PET) mixed in a mass ratio of 3:2.

[0110] 4 parts by weight of an organosilicon-graphene oxide composite modifier was added to improve the surface properties and mechanical properties of the material.

[0111] 6 parts by weight of a bio-based polylactic acid-carbon nanotube composite reinforcing agent is mixed in to enhance the strength and degradability of the material.

[0112] 5 parts by weight of nanocellulose-vermiculite composite filler was added to improve the barrier properties and thermal stability of the material.

[0113] 3 parts by weight of a ternary composite conductive agent of magnetic nanoparticles, polyaniline and carbon nanotubes was added to optimize the conductive and magnetic properties of the material.

[0114] 3 parts by weight of microencapsulated paraffin phase change material is added to play a role in toughening and temperature regulation.

[0115] 6 parts by weight of glass fibers (macrofibers), 4 parts by weight of aramid fibers (microfibers), and 3 parts by weight of nanocellulose fibers (nanofibers) were added for multi-scale fiber reinforcement.

[0116] An appropriate amount of titanate coupling agent is introduced as an interfacial compatibilizer to enhance the interfacial bonding between the fiber and the waste plastic.

[0117] Process implementation:

[0118] The waste plastic mixture was subjected to ultrasonic-radio frequency synergistic pretreatment with an ultrasonic power of 220W and a radio frequency power of 150W for 10 minutes to improve the reactivity of the material.

[0119] The pretreated waste plastics were premixed with other components in a high-speed mixer at a rotation speed of 1300 rpm for 33 minutes.

[0120] A reaction extrusion process assisted by a mixture of supercritical carbon dioxide and supercritical ethane was adopted. In a twin-screw extruder, the mixed supercritical fluid pressure was 13 MPa, the flow rate was 10 L / min, the extruder temperature was 160-180°C in zone 1, 180-200°C in zone 2, 200-220°C in zone 3, 220-240°C in zone 4, and the screw speed was 170 rpm.

[0121] During the extrusion process, photoinitiated in-situ polymerization was performed using a wavelength of 365 nm and a light intensity of 18 mW / cm 2 The waste plastic was irradiated with ultraviolet light for 25 minutes to initiate polymerization of the monomers on the surface and inside of the waste plastic.

[0122] Recycled plastic products are made using extrusion blow molding technology.

[0123] Performance Testing:

[0124] The bending strength reaches 80MPa, which is 40% higher than that of similar recycled materials that do not use the technology of the present invention. The synergistic effect of multi-scale fiber reinforcement and composite reinforcement significantly enhances the rigidity of the material.

[0125] Impact strength increased by 60% to 35 kJ / m 2 The microencapsulated paraffin phase change material and the organosilicon-graphene oxide composite modifier synergistically improved the toughness of the material.

[0126] The gas barrier property of the material has been greatly improved, and the oxygen permeability has been reduced by 45%. The barrier layer of nanocellulose-vermiculite composite filler effectively hinders the diffusion of oxygen molecules.

[0127] In the flame retardant performance test, the limiting oxygen index increased from 26% to 30%. The organic silicon-graphene oxide composite modifier and the nanocellulose-vermiculite composite filler formed a more stable barrier structure at high temperature, and synergistically improved the flame retardant performance with the original flame retardant system.

[0128] Compared with the modification method of PC and PET mixed recycled materials in the prior art, the bending strength of the embodiment of the present invention is improved by 18-25MPa and the impact strength is improved by 8-12kJ / m 2The gas barrier properties are significantly improved, and the limiting oxygen index is increased by 3-4 percentage points.

[0129] Example 6

[0130] Recipe Implementation:

[0131] The base material is 70 parts by weight of waste polypropylene (PP) and polyethylene (PE) mixed in a mass ratio of 2:3.

[0132] Adding 5 parts by weight of an organosilicon-reduced graphene composite modifier can improve the flexibility, conductivity and mechanical properties of the material.

[0133] 7 parts by weight of a bio-based polybutylene succinate-carbon nanotube composite reinforcing agent is mixed in to enhance the strength and degradability of the material.

[0134] 6 parts by weight of nanocellulose-montmorillonite composite filler was added to improve the barrier property and thermal stability of the material.

[0135] 4 parts by weight of a magnetic nanoparticle-polythiophene composite conductive agent is added to give the material magnetic response and conductive properties.

[0136] 4 parts by weight of microencapsulated palmitic acid phase change material was added to achieve temperature regulation and toughening effects.

[0137] 7 parts by weight of glass fiber (macrofiber), 5 parts by weight of basalt fiber (microfiber) and 4 parts by weight of nano alumina fiber (nanofibers) were added for multi-scale fiber reinforcement.

[0138] An appropriate amount of aluminate coupling agent is introduced as an interfacial compatibilizer to improve the interfacial bonding between the fiber and the waste plastic.

[0139] Process implementation:

[0140] The waste plastic mixture was subjected to laser-plasma synergistic pretreatment at a laser power of 300 W and a plasma power of 250 W for 12 minutes to enhance the surface activity of the material.

[0141] The pretreated waste plastics were premixed with other components in a high-speed mixer at a rotation speed of 1400 rpm for 30 minutes.

[0142] A supercritical propane-assisted reactive extrusion process is adopted. In a twin-screw extruder, the supercritical propane pressure is 14 MPa, the flow rate is 9 L / min, the extruder temperature is 170-190°C in zone 1, 190-210°C in zone 2, 210-230°C in zone 3, 230-250°C in zone 4, and the screw speed is 180 rpm.

[0143] During the extrusion process, photoinitiated in-situ polymerization modification was performed using a wavelength of 400 nm and a light intensity of 20 mW / cm2 The waste plastic was irradiated with ultraviolet light for 30 minutes to initiate polymerization of the monomers on the surface and inside the waste plastic.

[0144] The recycled plastic products are made by injection molding process.

[0145] Performance Testing:

[0146] The tensile strength reaches 52MPa, which is 45% higher than that of similar recycled materials without the technology of the present invention. The multi-scale fiber reinforcement and the composite reinforcement agent work together to strengthen the internal structure of the material.

[0147] The heat deformation temperature increased by 30°C to 130°C. The nanocellulose-montmorillonite composite filler and the organosilicon-reduced graphene composite modifier jointly improved the thermal stability of the material.

[0148] In the simulated natural environment aging test, after 1,500 hours of light, temperature and humidity changes, the mechanical property retention rate of the material reached 82%, while that of ordinary similar recycled materials was only 60%. Microencapsulated palmitic acid phase change material and organosilicon-reduced graphene composite modifier enhanced the material's weather resistance.

[0149] The surface resistance of the material is reduced to 10 6 Ω, with excellent antistatic properties. Magnetic nanoparticles-polythiophene composite conductive agent effectively improves the electrical properties of the material.

[0150] Compared with the conventional modification method of PP and PE mixed recycled materials in the prior art, the embodiments of the present invention improve the tensile strength by 15-22 MPa, significantly increase the heat deformation temperature, and increase the mechanical property retention rate after aging by 18-25%.

[0151] Example 7

[0152] Recipe Implementation:

[0153] The base material is waste polyvinyl chloride (PVC), 74 parts by weight.

[0154] 6 parts by weight of an organosilicon-graphene quantum dot composite modifier was added to improve the surface properties and electrical properties of the material.

[0155] 8 parts by weight of a bio-based polyhydroxybutyrate-carbon nanotube composite reinforcing agent is mixed in to enhance the strength and degradability of the material.

[0156] 7 parts by weight of a nanocellulose-kaolin composite filler was added to improve the barrier properties and thermal stability of the material.

[0157] 5 parts by weight of a magnetic nanoparticle-polyaniline-graphene composite conductive agent was added to optimize the conductive and magnetic properties of the material.

[0158] 5 parts by weight of microencapsulated stearic acid phase change material is added to play a role in toughening and temperature regulation.

[0159] 8 parts by weight of glass fiber (macrofiber), 6 parts by weight of aramid fiber (microfiber) and 5 parts by weight of nano titanium dioxide fiber (nanofiber) were added for multi-scale fiber reinforcement.

[0160] An appropriate amount of silane-titanate composite coupling agent is introduced as an interface compatibilizer to enhance the interface bonding between the fiber and the waste plastic. Process implementation:

[0161] The waste PVC was subjected to ultrasonic-microwave synergistic pretreatment with an ultrasonic power of 250W and a microwave power of 700W for 15 minutes to improve the reactivity of the material.

[0162] The pretreated waste PVC was premixed with other components in a high-speed mixer at a rotation speed of 1500 rpm for 30 minutes.

[0163] A reaction extrusion process assisted by a mixture of supercritical carbon dioxide and supercritical nitrogen was adopted. In a twin-screw extruder, the mixed supercritical fluid pressure was 15 MPa, the flow rate was 12 L / min, the extruder temperature was 180-200°C in zone 1, 200-220°C in zone 2, 220-240°C in zone 3, 240-260°C in zone 4, and the screw speed was 190 rpm.

[0164] During the extrusion process, photoinitiated in-situ polymerization was performed using a wavelength of 375 nm and a light intensity of 22 mW / cm 2 The waste plastic was irradiated with ultraviolet light for 35 minutes to initiate polymerization of the monomers on the surface and inside the waste plastic.

[0165] Recycled plastic products are made using extrusion molding technology.

[0166] Performance Testing:

[0167] The bending strength reaches 65MPa, which is 38% higher than that of PVC recycled materials that do not use the technology of the present invention. The synergistic effect of multi-scale fiber reinforcement and composite reinforcing agent significantly enhances the rigidity of the material.

[0168] Impact strength increased by 70% to 25 kJ / m 2 The microencapsulated stearic acid phase change material and the organosilicon-graphene quantum dot composite modifier synergistically improved the toughness of the material.

[0169] The gas barrier property of the material is greatly improved, and the water vapor transmission rate is reduced by 50%. The barrier layer of nanocellulose-kaolin composite filler effectively hinders the diffusion of water vapor molecules.

[0170] In the flame retardant performance test, the limiting oxygen index increased from 27% to 31%. The organic silicon-graphene quantum dot composite modifier and the nanocellulose-kaolin composite filler formed a more stable barrier structure at high temperature, and synergistically improved the flame retardant performance with the original flame retardant system.

[0171] Compared with the modification method of PVC recycled materials in the prior art, the bending strength of the embodiment of the present invention is improved by 15-20MPa and the impact strength is improved by 7-10kJ / m 2 The gas barrier properties are significantly improved, and the limiting oxygen index is increased by 3-4 percentage points.

[0172] Example 8

[0173] Recipe Implementation:

[0174] The base material is 76 parts by weight of waste polystyrene (PS) and polycarbonate (PC) mixed in a mass ratio of 4:1.

[0175] Adding 4 parts by weight of an organosilicon-fullerene composite modifier can improve the flexibility, conductivity and mechanical properties of the material.

[0176] 6 parts by weight of bio-based poly(hexanediol adipate)-carbon nanotube composite reinforcing agent was mixed in to enhance the strength and degradability of the material. 5 parts by weight of nanocellulose-bentonite composite filler was added to improve the barrier property and thermal stability of the material.

[0177] 3 parts by weight of a ternary composite conductive agent of magnetic nanoparticles, polypyrrole and carbon nanotubes is added to give the material magnetic response and conductive properties.

[0178] 3 parts by weight of microencapsulated lauric acid phase change material was added to achieve temperature regulation and toughening effects.

[0179] 6 parts by weight of glass fibers (macrofibers), 4 parts by weight of carbon fibers (microfibers), and 3 parts by weight of nanocellulose fibers (nanofibers) were added for multi-scale fiber reinforcement.

[0180] Introduce an appropriate amount of aluminate-silane composite coupling agent as an interface compatibilizer to improve the interface bonding between the fiber and the waste plastic. Process implementation:

[0181] The waste plastic mixture was subjected to RF-laser synergistic pretreatment at RF power of 180W and laser power of 350W for 10 minutes to enhance the surface activity of the material.

[0182] The pretreated waste plastics were premixed with other components in a high-speed mixer at a rotation speed of 1300 rpm for 32 minutes.

[0183] A supercritical carbon dioxide-assisted reactive extrusion process is adopted. In a twin-screw extruder, the supercritical carbon dioxide pressure is 13 MPa, the flow rate is 10 L / min, the extruder temperature is 160-180°C in zone 1, 180-200°C in zone 2, 200-220°C in zone 3, 220-240°C in zone 4, and the screw speed is 170 rpm.

[0184] During the extrusion process, photoinitiated in-situ polymerization was performed using a wavelength of 390 nm and a light intensity of 16 mW / cm 2 The waste plastic was irradiated with ultraviolet light for 28 minutes to initiate polymerization of the monomers on the surface and inside the waste plastic.

[0185] The recycled plastic products are made by injection molding process.

[0186] Performance Testing:

[0187] The tensile strength reaches 50MPa, which is 42% higher than that of similar recycled materials without the technology of the present invention. The multi-scale fiber reinforcement and the composite reinforcement agent work together to strengthen the internal structure of the material.

[0188] The thermal stability is significantly improved, and the temperature at which the thermal weight loss is 5% is increased by 30°C. The nanocellulose-bentonite composite filler and the organosilicon-fullerene composite modifier jointly improve the thermal stability of the material.

[0189] In the simulated natural environment aging test, after 1,300 hours of light, temperature and humidity changes, the mechanical property retention rate of the material reached 80%, while that of ordinary similar recycled materials was only 58%. Microencapsulated lauric acid phase change material and silicone-fullerene composite modifier enhanced the material's weather resistance.

[0190] The surface resistance of the material is reduced to 107Ω, and it has good antistatic properties. The magnetic nanoparticle-polypyrrole-carbon nanotube ternary composite conductive agent effectively improves the electrical properties of the material.

[0191] Compared with the conventional modification method of PS and PC mixed recycled materials in the prior art, the embodiments of the present invention improve the tensile strength by 12-18 MPa, significantly improve the thermal stability, and increase the mechanical property retention rate after aging by 15-20%.

[0192] The barrier effect of nanocellulose-montmorillonite composite filler is significant. In the present invention, the novel organosilicon-graphene composite modifier organosilicon has low surface energy, good flexibility and weather resistance, and graphene has excellent mechanical properties, electrical conductivity and thermal conductivity. The purpose of compounding organosilicon and graphene is to use organosilicon to improve the surface properties and flexibility of waste plastics, and graphene to enhance the mechanical properties, electrical properties and thermal properties of waste plastics, so as to achieve multifunctional modification of waste plastics. Mechanism of action: Organosilicon molecules form a protective film with low surface energy on the surface of waste plastics, reduce surface tension, and improve the water resistance and weather resistance of the material. Graphene is evenly dispersed in the waste plastic matrix to form a three-dimensional network structure, enhance the mechanical properties of the material, and improve the electrical and thermal properties at the same time. Organosilicon and graphene interact through chemical bonds or physical adsorption to synergistically exert the modification effect. Synthesis method: Take tetraethyl orthosilicate and graphene oxide as raw materials. First, ultrasonically disperse graphene oxide in anhydrous ethanol to form a uniform dispersion. Then, ethyl orthosilicate and an appropriate amount of hydrochloric acid catalyst are added dropwise, and the reaction is stirred at 60-80°C for 6-8 hours. After the reaction is completed, the organosilicon-graphene composite modifier is obtained by centrifugation, washing, drying and other steps. This synthesis method refers to the relevant reports on organosilicon hydrolysis condensation and graphene surface modification. The bio-based polyester-carbon nanotube composite enhancer is renewable and degradable, and the carbon nanotubes have extremely high strength and modulus. The bio-based polyester is compounded with carbon nanotubes, and the environmental protection characteristics of the bio-based polyester and the high strength of the carbon nanotubes are utilized to enhance the mechanical properties of the waste plastics, while improving the environmental performance of the materials.

[0193] Mechanism of action: Bio-based polyester has good compatibility with waste plastics and can be evenly dispersed in the matrix. Carbon nanotubes are evenly distributed in waste plastics under the wrapping of bio-based polyester to form a reinforced skeleton. When the material is subjected to external force, carbon nanotubes can effectively transmit and disperse stress, significantly improving the strength and modulus of the material. Supercritical carbon dioxide has good solubility, diffusivity and compressibility. In the process of waste plastic recycling, supercritical carbon dioxide is used to assist reactive extrusion, aiming to improve the fluidity of the material, promote the progress of chemical reactions, improve the uniformity of dispersion of each component, while reducing processing temperature and pressure and energy consumption. Supercritical carbon dioxide can dissolve in waste plastics and additives, reduce the viscosity of the system, and improve the fluidity of the material. In the process of reactive extrusion, supercritical carbon dioxide promotes contact and reaction between reactants, and helps additives to be evenly dispersed in the waste plastic matrix. In addition, the compressibility of supercritical carbon dioxide enables better control of the morphology and structure of the material during the extrusion process. Plasma treatment can introduce active groups on the surface of waste plastics, and chemical grafting can graft functional molecules onto the surface of waste plastics, thereby improving the surface properties of waste plastics and compatibility with other components. Plasma treatment and chemical grafting are used in synergy to achieve deep modification of waste plastics. During plasma treatment, high-energy particles bombard the surface of waste plastics, breaking the surface molecular chains and generating active groups such as free radicals. Subsequently, a chemical grafting reaction is carried out, and functional molecules are grafted onto the surface of waste plastics by reacting with these active groups. For example, grafting molecules containing polar groups can improve the compatibility of waste plastics with polar additives; grafting molecules containing reactive groups can further participate in subsequent chemical reactions and enhance the performance of materials. Nanocellulose has the characteristics of high strength, high modulus, and high specific surface area, and montmorillonite has a unique layered structure and ion exchange properties. Nanocellulose is compounded with montmorillonite, and the mechanical properties, barrier properties and thermal stability of waste plastics are improved by utilizing the reinforcing effect of nanocellulose and the barrier properties of montmorillonite. Nanocellulose forms a network structure in waste plastics to enhance the mechanical properties of the material. The lamellar structure of montmorillonite is evenly dispersed in the waste plastic matrix to form a barrier layer, which hinders the diffusion of gases and small molecules and improves the barrier properties of the material. At the same time, the synergistic effect of nanocellulose and montmorillonite can improve the thermal stability of the material and inhibit the decomposition of waste plastics at high temperatures. Nanocellulose suspension and montmorillonite dispersion are used as raw materials. The montmorillonite dispersion is slowly added dropwise to the nanocellulose suspension and stirred and mixed for 1-2 hours at room temperature. Then an appropriate amount of cross-linking agent, such as glutaraldehyde, is added and the stirring reaction is continued for 2-3 hours. After the reaction is completed, the nanocellulose-montmorillonite composite filler is obtained by steps such as centrifugation, washing, and drying. This synthetic method refers to the relevant reports on the composite of nanocellulose and montmorillonite.Photoinitiators are used to generate free radicals under light, which trigger monomers to polymerize in situ on the surface or inside of waste plastics to form a polymer layer that is tightly bonded to the waste plastics, thereby improving the performance of waste plastics. This technology can achieve precise control of the performance of waste plastics without changing the original structure of the waste plastics. Photoinitiators decompose and generate free radicals under light of a specific wavelength, and these free radicals trigger monomers to polymerize. The polymerization reaction takes place on the surface or inside of the waste plastics, and the formed polymer is tightly bonded to the waste plastics through chemical bonds or physical entanglements. For example, a layer of polymer coating with special properties is formed on the surface of waste plastics, which can improve its wear resistance, corrosion resistance and other properties; in situ polymerization inside the waste plastics can enhance the mechanical properties and thermal stability of the material. Magnetic nanoparticles have good magnetic properties, and polyaniline has excellent conductivity and environmental stability. Magnetic nanoparticles are compounded with polyaniline, and the magnetism of magnetic nanoparticles is used to achieve magnetic manipulation of the material. The conductivity of polyaniline gives the waste plastics conductive properties and improves the stability of the material. Magnetic nanoparticles are evenly dispersed in the polyaniline matrix to form a composite conductive agent. Under the action of an external magnetic field, magnetic nanoparticles can drive the composite conductive agent to align in the waste plastic, forming a conductive path and improving the conductivity of the material. At the same time, the presence of polyaniline can protect the magnetic nanoparticles, prevent them from oxidation and agglomeration, and improve the stability of the material. Microencapsulated phase change materials can absorb or release heat when the temperature changes, thereby regulating the temperature of the material. By adding microencapsulated phase change materials to waste plastics and utilizing their phase change characteristics, the toughness of the material can be improved while regulating the temperature of the material's use environment, thereby broadening the application range of the material.

[0194] Mechanism of action: Microencapsulated phase change materials are evenly dispersed in the waste plastic matrix. When the ambient temperature rises, the phase change material absorbs heat and undergoes phase change, changing from solid to liquid. The absorbed heat is stored in the form of latent heat, thereby reducing the temperature rise of the material. When the ambient temperature drops, the phase change material changes from liquid to solid, releasing the stored heat and increasing the temperature of the material. When the material is impacted by external force, the microencapsulated phase change material can absorb energy through phase change and play a toughening role. Fibers of different scales, such as nanofibers, micron fibers and macro fibers, are used to enhance waste plastics. At the same time, through interface optimization technology, the interface compatibility between fibers and waste plastics is improved, the synergistic enhancement effect of multi-scale fibers is achieved, and the mechanical properties of waste plastics are significantly improved. Nanofibers form a nano-level reinforcement network in waste plastics, which can effectively hinder the movement of molecular chains and improve the strength and modulus of the material. Micron fibers and macro fibers enhance the mechanical properties of materials on a larger scale. Through interface optimization technology, such as surface treatment of fibers and addition of interface compatibilizers, the interfacial bonding force between fibers and waste plastics is improved, so that the fibers can better transfer stress and achieve synergistic enhancement of multi-scale fibers.

[0195] Example 9

[0196] Design of new organic compound modifiers:

[0197] An organic compound named 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid (MAPBA) was designed. The design principle is that the acryloxy group can undergo free radical addition reaction with the unsaturated bonds in waste plastics to achieve chemical bonding with the base material. The introduction of 2-methyl-3-propoxy increases the steric hindrance and flexibility of the molecule, which helps to improve the processing properties of the material. The benzoic acid group can improve the thermal stability and rigidity of the material.

[0198] In terms of mechanism of action, the acryloxy group reacts with waste plastics during processing to form a chemical bond, which enhances the binding force between the modifier and the base material. The 2-methyl-3-propoxy group makes the molecular chain flexible, reduces the melt viscosity of the material, and improves processing fluidity. The benzoic acid group can stabilize the molecular structure at high temperatures and inhibit thermal decomposition.

[0199] Synthesis method: 3-hydroxybenzoic acid and 2-methyl-3-chloropropene are used as raw materials, and heated under reflux reaction for 4-6 hours under alkaline conditions, such as in an ethanol solution of sodium hydroxide, to generate 3-(2-methyl-3-hydroxypropoxy)benzoic acid. Then, it is reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid. This synthesis method refers to the reports on the nucleophilic substitution reaction of phenols and halogenated hydrocarbons and the esterification reaction of alcohols and acyl chlorides.

[0200] Recipe Implementation:

[0201] The base material is 75 parts by weight of waste polyethylene terephthalate (PET).

[0202] 8 parts by weight of MAPBA were added as a modifier.

[0203] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0204] 6 parts by weight of glass fiber was mixed as a reinforcing agent.

[0205] 3 parts by weight of ultraviolet absorber were introduced.

[0206] Process implementation:

[0207] The waste PET was crushed and premixed with other formulation components in a high-speed mixer for 30 minutes.

[0208] Enter into the twin-screw extruder, melt blend at 240-260°C, and the screw speed is 170rpm.

[0209] During the blending process, ultrasonic treatment was used for 20 minutes to promote uniform dispersion of the components.

[0210] The recycled material prototype was made using the injection molding process.

[0211] Synergistic test:

[0212] Compared with the same formula material without MAPBA, the tensile strength of the material with MAPBA increased by 28% to 78MPa. MAPBA and glass fiber synergistically strengthen the internal structure of the material.

[0213] In the thermal stability test, the initial decomposition temperature increased by 20°C. The benzoic acid group and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically effectively inhibited the decomposition of the material at high temperatures.

[0214] Compared with the materials modified with common acryloxy compounds in the prior art, the tensile strength of the material of this embodiment is increased by 10-15%, and the initial decomposition temperature is increased by 10-15° C. In the weather resistance test, after 1200 hours of artificial accelerated aging, the mechanical property retention rate of the material is 10-15% higher than that of similar modified materials in the prior art.

[0215] Example 10

[0216] Design of new organic compound modifiers:

[0217] An organic compound named 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid (BMOPA) was designed. The butenoyloxy group can undergo addition reaction with waste plastics to achieve chemical bonding. The 2-methoxypropoxy group increases the polarity and flexibility of the molecule, which helps to improve the solubility and processing properties of the material. The phenylacetic acid group can enhance the interaction between molecules and improve the strength and thermal stability of the material.

[0218] The mechanism of action is that the butylene acyloxy group reacts with the unsaturated bonds of the waste plastic during processing to form a stable chemical bond. The 2-methoxypropoxy group reduces the melt viscosity of the material, making processing smoother. The phenylacetic acid group interacts with other molecules through hydrogen bonds and van der Waals forces, enhancing the cohesion of the material.

[0219] Synthesis method: 4-hydroxyphenylacetic acid and 3-butenoyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to generate 4-(3-butenoyloxy)phenylacetic acid. Then, it is reacted with 2-methoxy-3-chloropropane under alkaline conditions, such as in a methanol solution of potassium hydroxide, and heated under reflux for 3-5 hours to obtain 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid. This synthesis method refers to the reports on the esterification reaction of acyl chloride with phenolic acid and the nucleophilic substitution reaction of halogenated hydrocarbons with phenol salts.

[0220] Recipe Implementation:

[0221] Use waste polypropylene (PP) as base material, 72 parts by weight.

[0222] 9 parts by weight of BMOPA were added as a modifier.

[0223] 11 parts by weight of a magnesium hydroxide-aluminum hydroxide composite flame retardant was added.

[0224] 7 parts by weight of carbon fiber was mixed as a reinforcing agent.

[0225] 2 parts by weight of an antioxidant were introduced.

[0226] Process implementation:

[0227] The waste PP was crushed and premixed with other formulation components in a high-speed mixer for 32 minutes.

[0228] Enter into the twin-screw extruder, melt blend at 170-190°C, and the screw speed is 155rpm.

[0229] During the blending process, microwave radiation treatment was used for 15 minutes to promote uniform dispersion and chemical reaction of each component.

[0230] The recycled material sample is made using extrusion molding technology.

[0231] Synergistic test:

[0232] Compared with the same formula material without BMOPA, the bending strength of the material with BMOPA increased by 27% to 63MPa. BMOPA works synergistically with carbon fiber to enhance the rigidity of the material.

[0233] In the flame retardant performance test, the limiting oxygen index increased from 25% to 28%. The phenylacetic acid group of BMOPA synergistically acts with the magnesium hydroxide-aluminum hydroxide composite flame retardant to form a more stable flame retardant system at high temperatures.

[0234] Compared with the materials modified by ordinary crotonyloxy compounds in the prior art, the bending strength of the material of this embodiment is increased by 10-14%, and the limiting oxygen index is increased by 2-3 percentage points. In the oxidation resistance test, the oxidation induction time of the material under accelerated oxidation conditions is extended by 10-14 minutes compared with similar modified materials in the prior art.

[0235] Embodiment 11

[0236] Design of new organic compound modifiers:

[0237] An organic compound named 3-(2-vinyl-3-acryloyloxy) methyl benzoate (VAPMB) was designed. Both vinyl and acryloyloxy groups can undergo addition reactions with waste plastics to enhance the binding force with the base material. The methyl benzoate group can improve the thermal stability and rigidity of the material, while the presence of the methyl ester group may affect the crystallization and processing properties of the material.

[0238] The mechanism of action is that the vinyl and acryloxy groups react with the unsaturated bonds of the waste plastic during processing to form a three-dimensional network structure, which enhances the strength of the material. The methyl benzoate group can stabilize the molecular structure at high temperatures and inhibit thermal decomposition.

[0239] Synthesis method: 3-hydroxybenzoic acid methyl ester and 2-vinyl-3-chloropropene are used as raw materials, and heated under reflux reaction for 5-7 hours under alkaline conditions, such as in an aqueous solution of sodium carbonate, to generate 3-(2-vinyl-3-hydroxy)benzoic acid methyl ester. Then, it is reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain 3-(2-vinyl-3-acryloyloxy)benzoic acid methyl ester. This synthesis method refers to the reports on the nucleophilic substitution reaction of phenol esters with halogenated hydrocarbons and the esterification reaction of alcohols with acyl chlorides.

[0240] Recipe Implementation:

[0241] Use waste polycarbonate (PC) as base material, 76 parts by weight.

[0242] 7 parts by weight of VAPMB were added as a modifier.

[0243] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0244] 5 parts by weight of aramid fiber was mixed as a reinforcing agent.

[0245] 3 parts by weight of light stabilizer were introduced.

[0246] Process implementation:

[0247] The waste PC was crushed and premixed with other formulation components in a high-speed mixer for 31 minutes.

[0248] Enter into the twin-screw extruder, melt blend at 220-240°C, and the screw speed is 165rpm.

[0249] During the blending process, high-voltage pulse electric field treatment was used with an electric field strength of 3 kV / cm and a pulse frequency of 20 Hz for 20 minutes to promote the orientation arrangement and interface bonding of each component.

[0250] The recycled material prototype was made using the injection molding process.

[0251] Synergistic test:

[0252] Compared with the same formula material without VAPMB, the impact strength of the material with VAPMB increased by 30% to 33kJ / m 2 VAPMB works synergistically with aramid fibers to enhance the toughness of the material.

[0253] In the thermal stability test, the initial decomposition temperature increased by 22°C. The methyl benzoate group of VAPMB and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically inhibited the decomposition of the material at high temperatures.

[0254] Compared with the materials modified by ordinary vinyl and acryloxy compounds in the prior art, the impact strength of the material of this embodiment is increased by 12-16%, and the initial decomposition temperature is increased by 12-16° C. In the weather resistance test, after 1400 hours of artificial accelerated aging, the mechanical property retention rate of the material is 12-16% higher than that of similar modified materials in the prior art.

[0255] Example 12

[0256] Design of new organic compound modifiers:

[0257] An organic compound named 4-(3-methyl-2-butenoyloxy-2-ethoxy) ethyl phenylpropionate (MBEPP) was designed. The methyl-2-butenoyloxy group can undergo an addition reaction with waste plastics to achieve chemical bonding. The 2-ethoxy group increases the flexibility and polarity of the molecule, which helps to improve the processing performance and solubility of the material. The ethyl phenylpropionate group can enhance the thermal stability and mechanical properties of the material. The mechanism of action is that the methyl-2-butenoyloxy group reacts with the unsaturated bonds of the waste plastics during processing to form stable chemical bonds. The 2-ethoxy group reduces the melt viscosity of the material, making processing smoother. The ethyl phenylpropionate group enhances the cohesion and rigidity of the material through intermolecular interactions.

[0258] Synthesis method: 4-hydroxyphenylpropionic acid ethyl ester and methyl-2-butenoyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to generate 4-(3-methyl-2-butenoyloxy)phenylpropionic acid ethyl ester. Then, it is reacted with 2-ethoxy-3-chloropropane under alkaline conditions, such as in an ethanol solution of sodium hydroxide, and heated under reflux for 4-6 hours to obtain 4-(3-methyl-2-butenoyloxy-2-ethoxy)phenylpropionic acid ethyl ester. This synthesis method refers to the reports on the esterification reaction of acyl chloride and phenol ester and the nucleophilic substitution reaction of halogenated hydrocarbon and phenol salt.

[0259] Recipe Implementation:

[0260] The base material is waste polyvinyl chloride (PVC), 74 parts by weight.

[0261] 8 parts by weight of MBEPP was added as a modifier.

[0262] Add 10 parts by weight of magnesium hydroxide-aluminum hydroxide composite flame retardant.

[0263] 6 parts by weight of glass fiber was mixed as a reinforcing agent.

[0264] 2 parts by weight of ultraviolet absorber were introduced.

[0265] Process implementation:

[0266] The waste PVC was crushed and premixed with other formulation components in a high-speed mixer for 33 minutes.

[0267] Enter into the twin-screw extruder, melt blend at 160-180°C, and the screw speed is 160rpm.

[0268] During the blending process, ultrasonic and microwave treatments were used alternately, with an ultrasonic power of 220 W and a microwave power of 600 W. Each treatment lasted 5 minutes and was performed alternately 3 times to promote uniform dispersion and chemical reaction of the components.

[0269] The recycled material sample is made using extrusion molding technology.

[0270] Synergistic test:

[0271] Compared with the same formula material without MBEPP, the tensile strength of the material with MBEPP increased by 29% to 49MPa. MBEPP and glass fiber synergistically strengthen the internal structure of the material.

[0272] In the flame retardant performance test, the UL-94 vertical burning test was upgraded from V-2 to V-0. The ethyl phenylpropionate group of MBEPP synergistically with the magnesium hydroxide-aluminum hydroxide compound flame retardant forms a more effective flame retardant barrier at high temperatures.

[0273] Compared with the materials modified with ordinary methyl-2-butenoyloxy compounds in the prior art, the tensile strength of the material of this embodiment is increased by 11-15%, and in the UL-94 vertical burning test, it is improved from V-2 level to V-0 level. In the weather resistance test, after 1000 hours of artificial accelerated aging, the mechanical property retention rate of the material is 11-15% higher than that of similar modified materials in the prior art.

[0274] Example 13

[0275] Design of new organic compound modifiers:

[0276] An organic compound named 3-(4-vinyl-3-acryloyloxy)butyl benzoate (VAPBB) was designed. Vinyl and acryloyloxy groups can undergo addition reactions with waste plastics to enhance the bonding strength with the base material. The butyl benzoate group can improve the thermal stability and rigidity of the material, while the presence of the butyl ester group may affect the flexibility and processing performance of the material.

[0277] The mechanism of action is that vinyl and acryloyloxy groups react with the unsaturated bonds of waste plastics during processing to form a three-dimensional network structure and enhance the strength of the material. The butyl benzoate group can stabilize the molecular structure at high temperatures and inhibit thermal decomposition. Synthesis method: 3-hydroxybutyl benzoate and 4-vinyl-3-chloropropylene are used as raw materials. Under alkaline conditions, such as in an acetone solution of potassium carbonate, they are heated and refluxed for 6-8 hours to generate 3-(4-vinyl-3-hydroxy)butyl benzoate. Then it is reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain 3-(4-vinyl-3-acryloyloxy)butyl benzoate. This synthesis method refers to the reports on the nucleophilic substitution reaction of phenolic esters with halogenated hydrocarbons and the esterification reaction of alcohols with acyl chlorides.

[0278] Recipe Implementation:

[0279] Waste polystyrene (PS) is used as the base material, 78 parts by weight.

[0280] 6 parts by weight of VAPBB were added as a modifier.

[0281] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0282] 5 parts by weight of carbon fiber was mixed as a reinforcing agent.

[0283] 3 parts by weight of an antioxidant were introduced.

[0284] Process implementation:

[0285] After the waste PS was crushed, it was premixed with other formulation components in a high-speed mixer for 30 minutes.

[0286] Enter into the twin-screw extruder, melt blend at 180-200°C, and the screw speed is 170rpm.

[0287] During the blending process, ultrasonic treatment was used for 22 minutes to promote uniform dispersion of the components.

[0288] The recycled material prototype was made using the injection molding process.

[0289] Synergistic test:

[0290] Compared with the same formula material without VAPBB, the bending strength of the material with VAPBB increased by 28% to 59MPa. VAPBB works synergistically with carbon fiber to enhance the rigidity of the material.

[0291] In the thermal stability test, the initial decomposition temperature increased by 21°C. The butyl benzoate group of VAPBB and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically effectively inhibited the decomposition of the material at high temperatures.

[0292] Compared with the materials modified by ordinary vinyl and acryloxy compounds in the prior art, the bending strength of the material of this embodiment is increased by 10-14%, and the initial decomposition temperature is increased by 10-14° C. In the oxidation resistance test, the oxidation induction time of the material under accelerated oxidation conditions is extended by 10-14 minutes compared with similar modified materials in the prior art.

[0293] Embodiment 14

[0294] Design of new organic compound modifiers:

[0295] An organic compound named 4-(3-acryloyloxy-2-propoxy)phenylacetic acid propyl ester (APPPA) was designed. The acryloyloxy group can undergo addition reaction with waste plastics to achieve chemical bonding. The 2-propoxy group increases the flexibility and polarity of the molecule, which helps to improve the processing performance and solubility of the material. The phenylacetic acid propyl ester group can enhance the thermal stability and mechanical properties of the material.

[0296] The mechanism of action is that the acryloxy group reacts with the unsaturated bonds of the waste plastic during processing to form a stable chemical bond. The 2-propoxy group reduces the melt viscosity of the material, making processing smoother. The propyl phenylacetate group enhances the cohesion and rigidity of the material through intermolecular interactions.

[0297] Synthesis method: 4-hydroxyphenylacetic acid propyl ester and acryloyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to generate 4-(3-acryloyloxy)phenylacetic acid propyl ester. Then, it is reacted with 2-propoxy-3-chloropropane under alkaline conditions, such as in a methanol solution of potassium hydroxide, and heated under reflux for 4-6 hours to obtain 4-(3-acryloyloxy-2-propoxy-3-chloropropane. This synthesis method refers to the reports on the esterification reaction of acyl chloride and phenol ester and the nucleophilic substitution reaction of halogenated hydrocarbon and phenol salt.

[0298] Recipe Implementation:

[0299] Waste polybutylene terephthalate (PBT) is used as the base material, 73 parts by weight.

[0300] 7 parts by weight of APPPA was added as a modifier.

[0301] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0302] 6 parts by weight of glass fiber was mixed as a reinforcing agent.

[0303] 3 parts by weight of ultraviolet absorber were introduced.

[0304] Process implementation:

[0305] The waste PBT was crushed and premixed with other formulation components in a high-speed mixer for 30 minutes.

[0306] Enter into the twin-screw extruder, melt blend at 220-240°C, and the screw speed is 165rpm.

[0307] During the blending process, ultrasonic treatment was used for 20 minutes to promote uniform dispersion of the components.

[0308] The recycled material prototype was made using the injection molding process.

[0309] Synergistic test:

[0310] Compared with the same formula material without APPPA, the tensile strength of the material with APPPA increased by 26% to 80MPa. APPPA and glass fiber synergistically strengthen the internal structure of the material.

[0311] In the thermal stability test, the initial decomposition temperature increased by 18°C. The propyl phenylacetate group of APPPA and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically effectively inhibited the decomposition of the material at high temperatures.

[0312] Compared with the materials modified with common acryloxy compounds in the prior art, the tensile strength of the material of this embodiment is increased by 8-12%, and the initial decomposition temperature is increased by 8-12° C. In the weather resistance test, after 1200 hours of artificial accelerated aging, the mechanical property retention rate of the material is 8-12% higher than that of similar modified materials in the prior art.

[0313] Embodiment 15

[0314] Design of new organic compound modifiers:

[0315] An organic compound named 3-(2-methyl-3-butenoyloxy)propyl benzoate (MBPBA) was designed. The design principle is to use the addition reaction of the butylene oxy group with the unsaturated bonds in the waste plastic to achieve bonding with the base material. The introduction of the 2-methyl group increases steric hindrance, changes the arrangement and performance of the molecules, and the propyl benzoate group helps to improve the thermal stability and rigidity of the material. In terms of mechanism of action, the butylene oxy group reacts with the waste plastic during processing to form chemical bonds and enhance the binding force. The 2-methyl group affects the crystallization behavior and flexibility of the molecule, and the propyl benzoate group stabilizes the molecular structure at high temperatures and inhibits thermal decomposition.

[0316] Synthesis method: 3-hydroxybenzoic acid propyl ester and 2-methyl-3-butenoyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to obtain 3-(2-methyl-3-butenoyloxy)benzoic acid propyl ester. This synthesis method refers to the report on the esterification reaction of acyl chloride and phenol ester.

[0317] Recipe Implementation:

[0318] The base material is 70 parts by weight of waste polypropylene (PP) and polyethylene (PE) mixed in a mass ratio of 2:3.

[0319] 8 parts by weight of MBPBA were added as a modifier.

[0320] 11 parts by weight of a magnesium hydroxide-aluminum hydroxide composite flame retardant was added.

[0321] 7 parts by weight of carbon fiber was mixed as a reinforcing agent.

[0322] 2 parts by weight of an antioxidant were introduced.

[0323] Process implementation:

[0324] The waste plastics were mixed and crushed and then premixed with other formulation components in a high-speed mixer for 32 minutes.

[0325] Enter into the twin-screw extruder, melt blend at 170-190°C, and the screw speed is 155rpm.

[0326] During the blending process, microwave radiation treatment was used for 15 minutes to promote uniform dispersion and chemical reaction of each component.

[0327] The recycled material sample is made using extrusion molding technology.

[0328] Synergistic test:

[0329] Compared with the same formula material without MBPBA, the bending strength of the material with MBPBA increased by 27% to 65MPa. MBPBA works synergistically with carbon fiber to enhance the rigidity of the material.

[0330] In the flame retardant performance test, the limiting oxygen index increased from 25% to 28%. The propyl benzoate group of MBPBA synergistically acts with the magnesium hydroxide-aluminum hydroxide compound flame retardant to form a more stable flame retardant system at high temperatures.

[0331] Compared with the materials modified by ordinary crotonyloxy compounds in the prior art, the bending strength of the material of this embodiment is increased by 9-13%, and the limiting oxygen index is increased by 2-3 percentage points. In the oxidation resistance test, the oxidation induction time of the material under accelerated oxidation conditions is extended by 9-13 minutes compared with similar modified materials in the prior art.

[0332] Example 16

[0333] Design of new organic compound modifiers:

[0334] An organic compound named 4-(3-vinyl-2-acryloyloxy) butyl phenylpropionate (VABPB) was designed. Vinyl and acryloyloxy groups can undergo addition reactions with waste plastics to enhance the bonding strength with the base material. The butyl phenylpropionate group can improve the thermal stability and mechanical properties of the material.

[0335] The mechanism of action is that the vinyl and acryloxy groups react with the unsaturated bonds of the waste plastic during processing to form a three-dimensional network structure, which enhances the strength of the material. The butyl phenylpropionate group enhances the cohesion and rigidity of the material through intermolecular interactions and stabilizes the molecular structure at high temperatures.

[0336] Synthesis method: 4-hydroxyphenylpropionic acid butyl ester and 3-vinyl-2-chloropropylene are used as raw materials, and heated under reflux reaction for 5-7 hours under alkaline conditions, such as in an ethanol solution of sodium hydroxide, to generate 4-(3-vinyl-2-hydroxy)phenylpropionic acid butyl ester. Then, it is reacted with acryloyl chloride in the presence of triethylamine at 0-10°C for 2-3 hours to obtain 4-(3-vinyl-2-acryloyloxy)phenylpropionic acid butyl ester. This synthesis method refers to the nucleophilic substitution reaction of phenol esters and halogenated hydrocarbons and the esterification reaction of alcohols and acyl chlorides. Formula implementation:

[0337] Use waste polycarbonate (PC) as base material, 76 parts by weight.

[0338] 7 parts by weight of VABPB were added as a modifier.

[0339] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0340] 5 parts by weight of aramid fiber was mixed as a reinforcing agent.

[0341] 3 parts by weight of light stabilizer were introduced.

[0342] Process implementation:

[0343] The waste PC was crushed and premixed with other formulation components in a high-speed mixer for 31 minutes.

[0344] Enter into the twin-screw extruder, melt blend at 220-240°C, and the screw speed is 165rpm.

[0345] During the blending process, high-voltage pulse electric field treatment was used with an electric field strength of 3 kV / cm and a pulse frequency of 20 Hz for 20 minutes to promote the orientation arrangement and interface bonding of each component.

[0346] The recycled material prototype was made using the injection molding process.

[0347] Synergistic test:

[0348] Compared with the same formula material without VABPB, the impact strength of the material with VABPB increased by 30% to 35kJ / m 2 . VABPB works synergistically with aramid fibers to enhance the toughness of the material.

[0349] In the thermal stability test, the initial decomposition temperature increased by 22°C. The butyl phenylpropionate group of VABPB and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically inhibited the decomposition of the material at high temperatures.

[0350] Compared with the materials modified by ordinary vinyl and acryloxy compounds in the prior art, the impact strength of the material of this embodiment is increased by 12-16%, and the initial decomposition temperature is increased by 12-16° C. In the weather resistance test, after 1400 hours of artificial accelerated aging, the mechanical property retention rate of the material is 12-16% higher than that of similar modified materials in the prior art.

[0351] Embodiment 17

[0352] Design of new organic compound modifiers:

[0353] An organic compound named 3-(4-methyl-3-butenoyloxy)ethyl benzoate (MBEBA) was designed. The methyl-butenoyloxy group can undergo addition reaction with waste plastics to achieve chemical bonding. The ethyl benzoate group can enhance the thermal stability and rigidity of the material.

[0354] The mechanism of action is that the methyl-butylene acyloxy group reacts with the unsaturated bonds of waste plastics during processing to form stable chemical bonds. The ethyl benzoate group stabilizes the molecular structure at high temperatures, inhibits thermal decomposition, and at the same time enhances the cohesion of the material through intermolecular interactions.

[0355] Synthesis method: 3-hydroxybenzoic acid ethyl ester and 4-methyl-3-butenoyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to obtain 3-(4-methyl-3-butenoyloxy)benzoic acid ethyl ester. This synthesis method refers to the report on the esterification reaction of acyl chloride and phenol ester.

[0356] Recipe Implementation:

[0357] The base material is waste polyvinyl chloride (PVC), 74 parts by weight.

[0358] 8 parts by weight of MBEBA were added as a modifier.

[0359] Add 10 parts by weight of magnesium hydroxide-aluminum hydroxide composite flame retardant.

[0360] 6 parts by weight of glass fiber was mixed as a reinforcing agent.

[0361] 2 parts by weight of ultraviolet absorber were introduced.

[0362] Process implementation:

[0363] The waste PVC was crushed and premixed with other formulation components in a high-speed mixer for 33 minutes.

[0364] Enter into the twin-screw extruder, melt blend at 160-180°C, and the screw speed is 160rpm.

[0365] During the blending process, ultrasonic and microwave treatments were used alternately, with an ultrasonic power of 220 W and a microwave power of 600 W. Each treatment lasted 5 minutes and was performed alternately 3 times to promote uniform dispersion and chemical reaction of the components.

[0366] The recycled material sample is made using extrusion molding technology.

[0367] Synergistic test:

[0368] Compared with the same formula material without MBEBA, the tensile strength of the material with MBEBA increased by 29% to 50MPa. MBEBA and glass fiber synergistically strengthen the internal structure of the material.

[0369] In the flame retardant performance test, the UL-94 vertical burning test was upgraded from V-2 to V-0. The ethyl benzoate group of MBEBA works synergistically with the magnesium hydroxide-aluminum hydroxide compound flame retardant to form a more effective flame retardant barrier at high temperatures.

[0370] Compared with the materials modified with ordinary methyl-butylene oxy compounds in the prior art, the tensile strength of the material of this embodiment is increased by 11-15%, and in the UL-94 vertical burning test, it is improved from V-2 level to V-0 level. In the weather resistance test, after 1000 hours of artificial accelerated aging, the mechanical property retention rate of the material is 11-15% higher than that of similar modified materials in the prior art.

[0371] Embodiment 18

[0372] Design of new organic compound modifiers:

[0373] An organic compound named 4-(3-acryloyloxy-2-ethoxy)phenylacetic acid methyl ester (AEPPM) was designed. The acryloxy group can undergo addition reaction with waste plastics to achieve chemical bonding. The 2-ethoxy group increases the flexibility and polarity of the molecule, which helps to improve the processing performance and solubility of the material. The methyl phenylacetate group can enhance the thermal stability and mechanical properties of the material.

[0374] The mechanism of action is that the acryloxy group reacts with the unsaturated bonds of the waste plastic during processing to form a stable chemical bond. The 2-ethoxy group reduces the melt viscosity of the material, making processing smoother. The methyl phenylacetate group enhances the cohesion and rigidity of the material through intermolecular interactions.

[0375] Synthesis method: 4-hydroxyphenylacetic acid methyl ester and acryloyl chloride are used as raw materials, and reacted at 0-10°C for 2-3 hours in the presence of triethylamine to generate 4-(3-acryloyloxy)phenylacetic acid methyl ester. Then, it is reacted with 2-ethoxy-3-chloropropane under alkaline conditions, such as in a methanol solution of potassium hydroxide, and heated under reflux for 4-6 hours to obtain 4-(3-acryloyloxy-2-ethoxy)phenylacetic acid methyl ester. This synthesis method refers to the reports on the esterification reaction of acyl chloride and phenol ester and the nucleophilic substitution reaction of halogenated hydrocarbon and phenol salt. Formula implementation:

[0376] Waste polystyrene (PS) is used as the base material, 78 parts by weight.

[0377] 6 parts by weight of AEPPM were added as a modifier.

[0378] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0379] 5 parts by weight of carbon fiber was mixed as a reinforcing agent.

[0380] 3 parts by weight of an antioxidant were introduced.

[0381] Process implementation:

[0382] After the waste PS was crushed, it was premixed with other formulation components in a high-speed mixer for 30 minutes.

[0383] Enter into the twin-screw extruder, melt blend at 180-200°C, and the screw speed is 170rpm.

[0384] During the blending process, ultrasonic treatment was used for 22 minutes to promote uniform dispersion of the components.

[0385] The recycled material prototype was made using the injection molding process.

[0386] Synergistic test:

[0387] Compared with the same formula material without AEPPM, the bending strength of the material with AEPPM increased by 28% to 60MPa. AEPPM works synergistically with carbon fiber to enhance the rigidity of the material.

[0388] In the thermal stability test, the initial decomposition temperature increased by 21°C. The methyl phenylacetate group of AEPPM and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically effectively inhibited the decomposition of the material at high temperatures.

[0389] Compared with the materials modified by ordinary acryloxy-containing compounds in the prior art, the bending strength of the material of this embodiment is increased by 10-14%, and the initial decomposition temperature is increased by 10-14° C. In the oxidation resistance test, the oxidation induction time of the material under accelerated oxidation conditions is extended by 10-14 minutes compared with similar modified materials in the prior art.

[0390] Embodiment 19

[0391] Design of new organic compound modifiers:

[0392] An organic compound named 3-(2-acryloyloxy-3-methoxy) isopropyl benzoate (APMIB) was designed. The acryloxy group can undergo addition reaction with waste plastics to achieve chemical bonding. The 3-methoxy group increases the polarity of the molecule, and the isopropyl benzoate group can improve the thermal stability and rigidity of the material.

[0393] The mechanism of action is that the acryloyloxy group reacts with the unsaturated bonds of waste plastics during processing to form stable chemical bonds. The 3-methoxy group affects the solubility and processing properties of the molecule, and the isopropyl benzoate group stabilizes the molecular structure at high temperatures and inhibits thermal decomposition. Synthesis method: Using 3-hydroxybenzoic acid isopropyl ester and 2-acryloyloxy-3-chloropropane as raw materials, under alkaline conditions, such as in an ethanol solution of sodium hydroxide, heat and reflux for 4-6 hours to generate 3-(2-acryloyloxy-3-methoxy)benzoic acid isopropyl ester. This synthesis method refers to the report on the nucleophilic substitution reaction of phenolic esters and halogenated hydrocarbons.

[0394] Recipe Implementation:

[0395] The base material is 75 parts by weight of waste polyethylene terephthalate (PET) and polycarbonate (PC) mixed in a mass ratio of 3:2.

[0396] 7 parts by weight of APMIB were added as a modifier.

[0397] 10 parts by weight of a magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant was added.

[0398] 6 parts by weight of glass fiber was mixed as a reinforcing agent.

[0399] 3 parts by weight of ultraviolet absorber were introduced.

[0400] Process implementation:

[0401] After the waste plastics are mixed and crushed, they are premixed with other formulation components in a high-speed mixer for 30 minutes.

[0402] Enter into the twin-screw extruder, melt blend at 230-250°C, and the screw speed is 165rpm.

[0403] During the blending process, ultrasonic treatment was used for 20 minutes to promote uniform dispersion of the components.

[0404] The recycled material prototype was made using the injection molding process.

[0405] Synergistic test:

[0406] Compared with the same formula material without APMIB, the tensile strength of the material with APMIB increased by 27% to 82MPa. APMIB and glass fiber synergistically strengthened the internal structure of the material.

[0407] In the thermal stability test, the initial decomposition temperature increased by 20°C. The isopropyl benzoate group of APMIB and the magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant synergistically inhibited the decomposition of the material at high temperatures.

[0408] Compared with the materials modified with common acryloxy compounds in the prior art, the tensile strength of the material of this embodiment is increased by 9-13%, and the initial decomposition temperature is increased by 9-13° C. In the weather resistance test, after 1200 hours of artificial accelerated aging, the mechanical property retention rate of the material is 9-13% higher than that of similar modified materials in the prior art.

[0409] Embodiment 20

[0410] The structure, composition and properties of the material are confirmed through a variety of analytical techniques. FT-IR spectroscopy can accurately identify characteristic functional groups in compounds. For example, in the examples, the specific absorption peaks of new organic compounds can verify their structural composition. 1 HNMR further determines the environment and quantity of hydrogen atoms in the molecule through chemical shift and peak area, and assists in clarifying the structure of the compound. Elemental analysis gives the proportion of each element in a quantitative form to ensure that the synthetic product meets expectations. These technologies confirm each other and ensure from different angles that the newly synthesized modifiers and recycled materials have accurate chemical structures and synergistic effects, as shown in Tables 1 and 2.

[0411]

[0412]

[0413]

[0414]

[0415]

[0416] Table 2 Characterization verification results

[0417]

[0418]

Claims

1. A method for preparing recycled waste plastic materials, characterized in that: The following steps are involved: Base material selection: waste plastics are selected as the base material, and the waste plastics include but are not limited to polyethylene terephthalate (PET), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polycarbonate (PC), polyethylene (PE), polybutylene terephthalate (PBT) and mixtures thereof, with a weight portion of 70-78 parts; Additive addition: Add a variety of functional additives to the base material, and the weight proportion of each functional additive is as follows: 3-6 parts by weight of organosilicon-graphene composite modifier; 4-8 parts by weight of bio-based polyester-carbon nanotube composite reinforcing agent; 3-7 parts by weight of nanocellulose-montmorillonite composite filler; 2-5 parts by weight of magnetic nanoparticle-polyaniline composite conductive agent; 2-5 parts by weight of microencapsulated phase change material; 5-8 parts by weight of glass fiber, 3-6 parts by weight of basalt fiber, 2-5 parts by weight of nano-silica fiber; Pretreatment: pretreatment of the waste plastics; Premixing: premixing the pretreated waste plastic with the functional additive in a high-speed mixer at a speed of 1200-1500 rpm for 30-35 minutes; Melt blending: melt blending is carried out in a twin-screw extruder using a supercritical fluid-assisted reactive extrusion process, wherein the supercritical fluid includes supercritical carbon dioxide, supercritical nitrogen, supercritical propane, supercritical ethane and mixtures thereof; Molding: Recycled plastic products are made by injection molding, extrusion molding or extrusion blow molding.

2. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: The organosilicon-graphene composite modifier is prepared by using tetraethyl orthosilicate and graphene oxide as raw materials, firstly ultrasonically dispersing the graphene oxide in anhydrous ethanol to form a uniform dispersion, then dropping tetraethyl orthosilicate and an appropriate amount of hydrochloric acid catalyst therein, stirring and reacting at 60-80° C. for 6-8 hours, and after the reaction is completed, centrifuging, washing, and drying to obtain the organosilicon-graphene composite modifier.

3. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: The bio-based polyester-carbon nanotube composite reinforcing agent is composited from bio-based polyester and carbon nanotubes. During preparation, the carbon nanotubes are uniformly dispersed in the bio-based polyester by stirring.

4. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: The nanocellulose-montmorillonite composite filler uses nanocellulose suspension and montmorillonite dispersion as raw materials. The montmorillonite dispersion is slowly added dropwise to the nanocellulose suspension, stirred and mixed for 1-2 hours at room temperature, and then a proper amount of cross-linking agent is added and stirred for reaction for 2-3 hours. After the reaction is completed, the filler is prepared by centrifugation, washing and drying steps.

5. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: The magnetic nanoparticle-polyaniline composite conductive agent is formed by uniformly dispersing magnetic nanoparticles in a polyaniline matrix.

6. A waste plastic recycled material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The recycled material has significantly improved tensile strength, flexural strength, impact strength, electrical conductivity, thermal stability, barrier properties, flame retardancy, weather resistance, and antioxidant properties.

7. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: The premixing step also includes adding a modifier which is one of the following compounds: 3-(2-methyl-3-acryloyloxypropoxy)benzoic acid, 4-(3-butenoyloxy-2-methoxypropoxy)phenylacetic acid, methyl 3-(2-vinyl-3-acryloyloxy)benzoate, ethyl 4-(3-methyl-2-butenoyloxy-2-ethoxy)phenylpropanoate, butyl 3-(4-vinyl-3-acryloyloxy)benzoate, propyl 4-(3-acryloyloxy-2-propoxy)phenylacetate, propyl 3-(2-methyl-3-butenoyloxy)benzoate, butyl 4-(3-vinyl-2-acryloyloxy)phenylpropanoate, ethyl 3-(4-methyl-3-butenoyloxy)benzoate, methyl 4-(3-acryloyloxy-2-ethoxy)phenylacetate, isopropyl 3-(2-acryloyloxy-3-methoxy)benzoate.

8. The method for preparing recycled waste plastic materials according to claim 1, characterized in that: Selection of base material and additives: waste plastic is used as the base material, with a weight ratio of 70-78 parts; Add 6-9 parts by weight of the novel organic compound modifier and other additives to the base material, including but not limited to: 10-11 parts by weight of magnesium hydroxide-aluminum hydroxide-phosphate melamine salt composite flame retardant; 10-11 parts by weight of magnesium hydroxide-aluminum hydroxide composite flame retardant; 5-7 parts by weight of glass fiber as a reinforcing agent; 5-7 parts by weight of carbon fiber as a reinforcing agent; Aramid fiber as a reinforcing agent 5-6 parts by weight; 2-3 parts by weight of ultraviolet absorber; 2-3 parts by weight of antioxidant; Light stabilizer 3 parts by weight or more; Premixing: crushing the waste plastics, and premixing with the novel organic compound modifier and other additives in a high-speed mixer at a speed of 1200-1500 rpm for 30-33 minutes; Melt blending: melt blending is carried out in a twin-screw extruder. The blending temperature is adjusted according to the type of waste plastics, such as 240-260℃ for waste PET, 170-190℃ for waste PP, 220-240℃ for waste PC, 160-180℃ for waste PVC, 180-200℃ for waste PS, 220-240℃ for waste PBT, and the screw speed is 155-170rpm. During the blending process, one or more of the following treatment methods are used to promote uniform dispersion, chemical reaction and orientation arrangement of each component: If ultrasonic treatment is used, the power is 220-250W and the treatment time is 20-22 minutes; If microwave radiation treatment is used, the power is 600-700W and the treatment time is 15 minutes; If high-voltage pulse electric field treatment is used, the electric field strength is 3kV / cm, the pulse frequency is 20Hz, and the treatment lasts for 20 minutes; If ultrasonic and microwave treatment are used alternately, the ultrasonic power is 220W, the microwave power is 600W, each treatment time is 5 minutes, and it is performed alternately 3 times; Molding: Recycled material samples are made by injection molding or extrusion molding.

Citation Information

Cited By

  • Composite plastic for geotechnical cloth and preparation method thereof

    CN120137300A

  • Environment-friendly PVC-U plastic pipe fitting and manufacturing method thereof

    CN120307709A

  • Continuous extruder for producing plastic hollow plate

    CN121552644A